A New Adjuvant MTOM Mediates Mycobacterium tuberculosis Subunit Vaccine to Enhance Th1-Type T Cell Immune Responses and IL-2+ T Cells - Yu, Qi; Wang, Xiaochun; Fan, Xionglin (Frontiers in Immunology, 2017)
The only licensed vaccine Mycobacterium bovis Bacillus Calmette-Guerin (BCG) cannot prevent the prevalence of tuberculosis (TB), which remains a major public health problem worldwide. A more effective TB vaccine than BCG is urgently needed. Subunit vaccine is a promising strategy and suitable adjuvants will benefit the development of effective TB subunit vaccines. MTO, consisting of monophosphoryl lipid A (MPLA), trehalose-6,6′-dibehenate (TDB) and MF59, was developed as an adjuvant of TB vaccine because of its ability to evoke the Th1-type T cell responses, while it is insufficient to induce single and multifunctional IL-2+ T cells, and has a limited ability to confer protection against Mycobacterium tuberculosis (M. tb) infection. Heat-killed Mycobacterium vaccae (Mv), which can evoke cytotoxic CD8+ and CD4+ T cells responses and has adjuvanticity, was here combined with MTO to produce a new adjuvant, called MTOM. The TB fusion protein Rv3407-PhoY2-Ag85A-Rv2626c-RpfB (WH121) was mixed with MTO, Mv, and MTOM to produce three subunit vaccines, and the protective efficacy and immune responses were compared in C57BL/6 mice. WH121/MTOM provided better protection against TB than the other two vaccines, matching the performance of BCG vaccine. MTOM showed stronger ability to increase single and multifunctional IL-2+ T cells and induce Th1-type responses than MTO or Mv. Therefore, MTOM might be a promising adjuvant that could contribute to the development of TB subunit vaccines.